Industrial Policy and Complexity Economics - Yap, Josef Teofisto T (Archīum Ateneo, 2024)
Mainstream theory underlying industrial policy highlights the neoclassical and structuralist approaches. The discussion on structuralist theories readily segues to complexity economics where industrial policy foments structural transformation by creating reinforcing feedback loops, particularly among manufacturing, exports, and investment. Empirical evidence is provided by applying panel cointegration analysis to investigate coevolution patterns among the following variables: investment-GDP ratio, exports-GDP ratio and manufacturing-GDP ratio. Econometric estimates show that there is indeed a long-run relationship that is bidirectional among the three variables. However, this is only a necessary condition for reinforcing feedback loops to materialize. Idiosyncratic factors in each country determine whether industrial policy has led to growth-oriented feedback loops. In the Philippines, despite interventions to boost manufacturing, no growth-oriented loop was established because of inadequate investment, particularly in infrastructure. Moreover, exports were hampered by the poor record in latching on to regional production networks. The Republic of Korea has had more success than Malaysia because it strengthened its innovation system. The missing link in Malaysia is own-technology creation.